Design and validation of a self-assessment tool for STE(A)M teachers in CLIL contexts - María José Luelmo del Castillo; Elvira Izquierdo Sánchez-Migallón; Virginia Vinuesa-Benítez; Nuria García-Manzanares (Journal of Technology and Science Education)
Incorporating STE(A)M and CLIL methodologies in bilingual education creates a learning environment where students develop scientific and technical knowledge while enhancing their linguistic and creative skills. By integrating these approaches, students can acquire essential skills, such as collaboration, communication, and critical thinking, which are essential for their future professional pursuits. Therefore, this article describes the process of creating a Self-assessment Tool (SAT) for implementing STE(A)M activities in CLIL environments and its validation through the Delphi method. The development, construction, and validation of CLIL-STE(A)M-SAT, an assessment rubric for teachers working in bilingual settings, and implementing STE(A)M methodology/activities in their classrooms, comprised two phases: 1) a literature review and design of a first draft of a rubric by the coordination group; 2) validation of the rubric involving the participation of experts. Twelve academic professionals assessed the clarity and feasibility of the proposed items in two rounds of email consultations. The final rubric consists of 23 items and is organized around two dimensions: the integration of STE(A)M and CLIL, and the design and planning of the teaching and learning process. It can be concluded that the CLIL-STE(A)M-SAT provides a potential path for future research by considering the feasibility of the tool being assessed by primary school educators at bilingual educational institutions that focus on STE(A)M disciplines.